Is your evidence robust enough? Questions for policy makers and practi tioners - Shaxson, Louise (Evidence & Policy: A Journal of Research, Debate and Practice, 2005)
This article examines the reasons we need evidence for policy, discuss es where evidence is needed in the policy-making process, and the natu re of the evidence base for strategy and policy. Working relationships between policy makers and their advisers are key: as policy makers co me from a variety of backgrounds, developing a common language helps s et discussions about the robustness of the evidence base on a sound fo oting. The article identifies five components of robustness, proposes a series of questions that could be used to address them and discusses the implications for the processes of policy making.